“We Are The Future”: Career Attitudes of MilleniGenZ College Students - Kelly M. Nguyen (Journal Committed to Social Change on Race and Ethnicity, 2023)
Millennials make up the largest segment of the workforce today and it is estimated that by 2025, 75% of the global workforce will comprise this emerging generation (Fry, 2018). In this current study, I examine the career attitudes of Latinx and Asian American Millennial and Gen Z college students to understand better how their unique college experiences- shaped by their familial, cultural, and personal backgrounds – can inform how they imagine their post-college trajectory. Specifically, I explore to what extent these sociocultural influences impact MilleniGenZ’s interest and attainment in leadership roles within their future careers. Two sets of surveys were administered. A 184-question survey was administered to college students in Southern California in 2017 (N=936), and in 2020, an updated 211-question survey was administered (N=742). The findings show the importance of providing better career resources (e.g., workshops, mentorship, networking opportunities) for MilleniGenZ during college, which will ease their transition into the workforce and potential leadership roles. The findings of the current study contribute to the existing literature by unpacking how complex sociocultural factors intersect to influence Latinx and Asian American college students’ career attitudes. Based on our findings, institutions, and organizations should incorporate diversity and inclusion considerations into the career planning process to support individuals in overcoming systemic barriers.